The Effectiveness of Using Novels in Learning Process to Improve the English Language Skills: A Systematic Review - Aprillya Alwien Suoth; Ceisy N. Wuntu; Olga A. Rorintulus (Journal of English Language Teaching, Literature and Culture, 2023)
In this era of technology, it helped us to easily get the other interesting learning media when the textbook become bored, especially through this pandemic of Covid 19. Most of learners want improvement of their language skills in their learning process, novel could be the interesting and powerful booster. This systematic review aims to examine the effectiveness of using novels in learning process to improve the language skills in English with showed the benefit and the weakness or problem that may encounter while using novel, and also the solution to optimize the use of novel in learning process. Previous research study about Novel in ELT published 2009 to 2021. Eleven previous studies were included and reviewed in terms: context, focus, and main findings. Result showed that mostly learner’s language skills (reading, writing, speaking, and listening) in English are increased. Novel also can improve grammar, vocabulary, pronunciation, social culture, critical thinking, personal growth, motivation and foster student- centre learning. This systematic review could help learners and teacher to consider the novel as a learning media that could be included in learning process to improve their language skills in English. For the future researcher, this systematic review could be another reference to improve the research about novel in ELT, especially the right and reliable solution to face the lack of novel when apply in ELT.